2017
DOI: 10.1108/jtf-04-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Building tourism-resilient communities by incorporating residents’ perceptions? A photo-elicitation study of tourism development in Bruges

Abstract: Purpose In a current trend of a growing amount of short city trips, it becomes crucial to understand how local residents perceive the presence of tourists and tourism in their cities and how their socio-cultural context influences those perceptions. The purpose of this paper is to contribute to this understanding which will enable the city planners to take actions to create the well-balanced and resilient communities in which the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 82 publications
1
25
0
1
Order By: Relevance
“…The opinions and perceptions of tourism impacts on a local scale are logically variable and heterogeneous. Nevertheless, it is key to understand how local residents perceive tourism development and how their demographic characteristics and their socioeconomic context influence their opinions [16]. The opinions of Toledo's residents regarding the impacts of tourism in their city are analyzed in this section, and the experimental results of the research are displayed in two subheadings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The opinions and perceptions of tourism impacts on a local scale are logically variable and heterogeneous. Nevertheless, it is key to understand how local residents perceive tourism development and how their demographic characteristics and their socioeconomic context influence their opinions [16]. The opinions of Toledo's residents regarding the impacts of tourism in their city are analyzed in this section, and the experimental results of the research are displayed in two subheadings.…”
Section: Resultsmentioning
confidence: 99%
“…In Toledo, the residents remark the benefits of tourism development over their costs. Just like Burges [16], the limits of overtourism have not been overstepped.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the intensification of urban tourism in the context of the entrepreneurial city (Blanco-Romero et al, 2018), the strengthening of the neoliberal urban agenda (Novy & Colomb, 2017) and conflicts around the socio-economic transformation of cities (Janusz et al, 2017) have led to the appearance of "critical voices [that] began to disturb and challenge the hitherto almost exclusively boosterist narratives surrounding tourism" (Novy, 2017, p. 60). While in no case can it be concluded that a global revolt against urban tourism is at play (Novy & Colomb, 2017) and although significant studies of very touristic cities have shown that tourist activity still enjoys far greater support than critiques (Janusz et al, 2017;UNWTO et al, 2018), there are indeed works that argue to the contrary, such as that of Blanco-Romero et al (2018) regarding Barcelona. Thus the idea becomes that the prior consensus around urban tourism can no longer be sustained, given that some (many?…”
Section: Introductionmentioning
confidence: 99%